MAKNA FILOSOFIS DAN HISTORIS KULINER DALAM NOVEL ARUNA DAN LIDAHNYA SEBAGAI BAHAN AJAR PEMINATAN DI SMA - Ghaisani Fildzah Amajida, - (2023)
MAKNA FILOSOFIS DAN HISTORIS KULINER DALAM NOVEL ARUNA DAN LIDAHNYA SEBAGAI BAHAN AJAR PEMINATAN DI SMA Ghaisani Fildzah Amajida NIM 1603473 Abstrak Pemanfaatan karya sastra dalam pembelajaran bahasa dan sastra pada sekolah menengah atas lazim dilakukan. Karya-karya sastra kanonis dan tua acapkali dijadikan pedoman dan contoh oleh pengajar. Siswa dituntut memahami dunia lama dan jauh dari kehidupan yang sedang dialami. Bergantinya era menghadirkan kreativitas baru dalam sastra yang kerap mengekplor hal-hal dekat dan esensial kehidupan. Makanan lazim dihidangkan di atas piring, kini tersaji dalam sastra. Fenomena tersebut dinamai gastronomi sastra. Makanan dan minuman merupakan produk budaya yang berkaitan erat dengan peradaban, sejarah, adat, dan sumber daya suatu wilayah, sehingga hidangan terkait dapat menjadi simbol atas wilayah tertentu. Penelitian ini akan menggali makna filosofis dan historis kuliner dalam novel Aruna dan Lidahnya. Penelitian ini menggunakan metode kualitatif, adapun pendekatan sastra yang digunakan adalah pendekatan mimetik. Berdasarkan analisis yang telah dilakukan, novel gastronomi sastra yang berjudul Aruna dan Lidahnya mengandung makna filosofis dan historis kuliner. Terdapat makna filosofis di balik kue delapan jam, yang merupakan sebuah petuah agar menggunakan waktu secara proporsional. Terdapat pula makna historis dari terciptanya pempek khas Palembang. Cara dan contoh proses penggalian makna filosofis dan historis terkait kemudian dijadikan bahan ajar mata pelajaran Bahasa Indonesia Peminatan kelas XI. Penilaian kelayakan modul dilakukan dengan penilaian materi, penyajian, bahasa, dan kesesuaian serta kemanfaatan pada literasi siswa. Hasil akhir penilaian kelayakan modul memperoleh nilai layak 86% dengan kategori sangat baik. Kata Kunci: bahan ajar, gastronomi sastra, makna filosofis, makna historis, novel GASTRONOMY STUDIES OF LITERATURE IN NOVEL "ARUNA DAN LIDAHNYA" AS UTILIZATION TEACHING MATERIAL OF LITERATURE APRECIATION IN HIGH SCHOOL Ghaisani Fildzah Amajida NIM 1603473 Abstract The use of literary works in language and literature learning in senior high schools is common. Old and canonical works of literature are often used as guidelines and examples by teachers. Students are required to understand the old world and far from the their life. Changing eras bring new creativity in literature which often explores things that are near and essential to life. Food is usually served on a plate, now it is presented in literature. This phenomenon called literary gastronomy. Food and drink are cultural products that are closely related to civilization, history, customs, and resources of a region, so that related dishes can become symbols of a particular region. This research will explore the philosophical and historical meanings of culinary in the novel Aruna dan Lidahnya. This study uses a qualitative method, while the literary approach used is mimetic approach. Based on the analysis that has been done, the literary gastronomic novel entitled Aruna dan Lidahnya contains a culinary philosophical and historical meaning. There is a philosophical meaning behind kue delapan jam, which is a suggestion to use time proportionally. There is also a historical meaning in the creation of the typical pempek Palembang. Methods and examples of the process of extracting related philosophical and historical meanings are then used as teaching materials for the Indonesian language specialization class XI. Assessment of the feasibility of the module is carried out by assessing the material, presentation, language, and suitability and benefits of student literacy. The final result of the feasibility assessment of the module obtained an appropriate score of 86% in the very good category. Keywords: historical meaning, literary gastronomy, novel, philosophical meaning, teaching materials GASTRONOMY STUDIES OF LITERATURE IN NOVEL "ARUNA DAN LIDAHNYA" AS UTILIZATION TEACHING MATERIAL OF LITERATURE APRECIATION IN HIGH SCHOOL Ghaisani Fildzah Amajida NIM 1603473 Abstract The use of literary works in language and literature learning in senior high schools is common. Old and canonical works of literature are often used as guidelines and examples by teachers. Students are required to understand the old world and far from the their life. Changing eras bring new creativity in literature which often explores things that are near and essential to life. Food is usually served on a plate, now it is presented in literature. This phenomenon called literary gastronomy. Food and drink are cultural products that are closely related to civilization, history, customs, and resources of a region, so that related dishes can become symbols of a particular region. This research will explore the philosophical and historical meanings of culinary in the novel Aruna dan Lidahnya. This study uses a qualitative method, while the literary approach used is mimetic approach. Based on the analysis that has been done, the literary gastronomic novel entitled Aruna dan Lidahnya contains a culinary philosophical and historical meaning. There is a philosophical meaning behind kue delapan jam, which is a suggestion to use time proportionally. There is also a historical meaning in the creation of the typical pempek Palembang. Methods and examples of the process of extracting related philosophical and historical meanings are then used as teaching materials for the Indonesian language specialization class XI. Assessment of the feasibility of the module is carried out by assessing the material, presentation, language, and suitability and benefits of student literacy. The final result of the feasibility assessment of the module obtained an appropriate score of 86% in the very good category. Keywords: historical meaning, literary gastronomy, novel, philosophical meaning, teaching materials